Reflector materials on benches act as supplementary sources of light in rucola cultivation - Cavalcante, Daniele Ferreira; Garcia, Akim Afonso; Vendrucolo, Eduardo Pradi; Seron, Cássio de Castro; Costa, Edilson; Bastos, Fernanda Espíndola Assumpção; Binotti, Flavio Ferreira da Silva; Battistuzzi Martins, Murilo; Seleguini, Alexander (Comunicata Scientiae, 2024)
The purpose of this work is to present an alternative to the use of lamp and light diodes to increase production systems that lead to better natural energy use and better plant development. The species Euruca sativa L. was used, cultivated under a protected environment, and four treatments were taken (control; glossy white laminate; bright red laminate; aluminized thermoreflective screen). Our findings showed to reduce the efficiency of laminated reflective materials in increasing rucola production. The application of the red laminate with greater efficiency, positive results with the increase of fresh matter and number of leaves, increasing the energy efficiency of the plant. Furthermore, the better use of natural light can reduce production costs, since the application of artificial light generates an increase in fixed production costs.